Growth factor stimulation for the healing of traumatic ulcers with liquid rice hull smoke - Arundina, Ira (J Taibah Univ Med Sci, 2021)
OBJECTIVE: The healing process of a traumatic ulcer requires growth factors to rebuild the lost tissue after the inflammatory process has been completed. Liquid rice hull smoke (LR-HS) has shown unique anti-inflammatory properties. This study analyses the role of LR-HS in growth factor stimulation for the healing of traumatic ulcers, such as fibroblast growth factor (FGF), vascular endothelial growth factor (VEGF), platelet-derived growth factor (PDGF), and collagen type 1 (COL-1) expression. METHODS: We obtained LR-HS from the pyrolysis of rice hulls. Traumatic ulcers were created in the labial fornix incisive inferior of Wistar rats and treated with LR-HS once a day for 3, 5, and 7 days. The control group was treated with sterile water. Each animal was sacrificed after treatment, and its labial fornix incisive inferior tissues were biopsied and immunohistochemically stained to examine FGF, VEGF, PDGF, and COL-1 expression. RESULT: The treatment of traumatic ulcers with LR-HS showed an increase in FGF, VEGF, PDGF, and COL-1 expression. VEGF expression increased under LR-HS treatment compared with the control 7-day treatment groups (p < 0.000). FGF and COL-1 expression increased under LR-HS treatment compared with the control 5- and 7-day treatment groups (p < 0.000). PDGF expression increased after treatment with LR-HS for 3, 5, and 7 days (p < 0.000). CONCLUSION: This study has demonstrated that LR-HS can induce the expression of growth factors during the healing of a traumatic ulcer using immunohistochemical staining. We suggest that LR-HS can be used as a herbal medicine for oral ulcer therapy.